2007
DOI: 10.1097/gco.0b013e3282f20aad
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in pregnancy: a review of current evidence

Abstract: Prepregnancy counselling and multidisciplinary team management is the key in achieving good pregnancy outcomes. There is emerging evidence about the safety and efficacy of oral hypoglycaemics like metformin in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 11 publications
(5 reference statements)
1
36
1
2
Order By: Relevance
“…3,6,8 Pregnancy establishes a state of insulin resistance to provide optimal glucose to the fetus, with tissue sensitivity to the hormone decreased by 50 to 60% by the third trimester due to elevated concentrations of insulin antagonists. 8,19,28 In addition, intra-abdominal fat, a predisposing risk factor for diabetes, increases during pregnancy. 3,8,28 Diabetic pregnant women have an increased risk of birth by cesarean section or operative vaginal delivery increasing the risk of maternal or fetal complications.…”
Section: Obesity and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6,8 Pregnancy establishes a state of insulin resistance to provide optimal glucose to the fetus, with tissue sensitivity to the hormone decreased by 50 to 60% by the third trimester due to elevated concentrations of insulin antagonists. 8,19,28 In addition, intra-abdominal fat, a predisposing risk factor for diabetes, increases during pregnancy. 3,8,28 Diabetic pregnant women have an increased risk of birth by cesarean section or operative vaginal delivery increasing the risk of maternal or fetal complications.…”
Section: Obesity and Inflammationmentioning
confidence: 99%
“…8,19,28 In addition, intra-abdominal fat, a predisposing risk factor for diabetes, increases during pregnancy. 3,8,28 Diabetic pregnant women have an increased risk of birth by cesarean section or operative vaginal delivery increasing the risk of maternal or fetal complications. 28 Intrapartum concerns for obese pregnancies include earlier admission, increased likelihood of induction of labor, difficulties with fetal monitoring and slow progression of labor.…”
Section: Obesity and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic pregnancies can be divided into two categories: those with pre-gestational or pre-existing diabetes mellitus in which the diagnosis is made in the pre-pregnancy state, and those with gestational diabetes mellitus (GDM). Pre-existing diabetes consists of type I (insulin-dependent) diabetes mellitus (IDDM)with an incidence of around 0.5%, and type 2 ( non-insulin-dependent) diabetes with an incidence of 2-3% ( Kapoor et al, 2007). The incidence of gestational diabetes mellitus differs in different populations (Gunton et al, 2001) and ethnic groups, and was shown to be as high as 13% in Chinese populations (Ko et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chronic complications such as vasculopathy in the pregnant women will not have time to evolve during the course of pregnancy. On the contrary, the diabetic hyperglycaemic states www.intechopen.com Gestational Diabetes 264 in gestational diabetes would stimulate fetal hyperinsulinemia, which would in turn lead to over-secretion of insulin-like growth factors (IGF), leading to overgrowth of the fetus (Kapoor et al, 2007). Thus, in contrast to pre-gestational diabetes mellitus, where vasculopathy is rife and the incidences of pre-eclampsia and fetal growth restriction are commonly encountered, GDM pregnancies pose a different category of pathophysiology and clinical risks.…”
Section: Introductionmentioning
confidence: 99%